2017
DOI: 10.1093/icvts/ivw429
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional cavopulmonary anastomosis with additional pulmonary blood flow: good or bad pre-Fontan strategy

Abstract: Our study demonstrates that APBF does not affect survival after BCPS or Fontan completion rate. APBF allows postponing the Fontan procedure without a negative effect on clinical status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
2
4
1
Order By: Relevance
“…Sugimoto and colleagues reported that patients who underwent BCPS with APBF had better-developed PA prior to the Fontan procedure, shorter pleural drainage duration, and shorter hospital stay after the Fontan procedure [25]. In our study, PA developed well and PAI was maintained at 485.1 ± 272.3 with low mean PAP (11.3 ± 3.8 mmHg) and Rp (1.1 ± 0.6 units) before the (10,16,21), PAP, Rp, and SVEDP were similar or lower, whereas PAI was superior in our study. There were no intrapulmonary shunts or atrioventricular valve regurgitations that required intervention by the Fontan procedure.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Sugimoto and colleagues reported that patients who underwent BCPS with APBF had better-developed PA prior to the Fontan procedure, shorter pleural drainage duration, and shorter hospital stay after the Fontan procedure [25]. In our study, PA developed well and PAI was maintained at 485.1 ± 272.3 with low mean PAP (11.3 ± 3.8 mmHg) and Rp (1.1 ± 0.6 units) before the (10,16,21), PAP, Rp, and SVEDP were similar or lower, whereas PAI was superior in our study. There were no intrapulmonary shunts or atrioventricular valve regurgitations that required intervention by the Fontan procedure.…”
Section: Discussionsupporting
confidence: 56%
“…These short-term outcomes have been well discussed, whereas little is known about long-term outcomes in patients who underwent BCPS with APBF. Thus, whether APBF should be preserved at the time of BCPS remains controversial [7][8][9][10].…”
mentioning
confidence: 99%
“…SVEDP decreased from 11.4 ± 3.2 to 8.2 ± 3.0 mmHg during the interstage of the Fontan procedure. In comparison with other reports (10,16,21), PAP, Rp, and SVEDP were similar or lower, whereas PAI was superior in our study. There were no intrapulmonary shunts or atrioventricular valve regurgitations that required intervention by the Fontan procedure.…”
Section: Discussioncontrasting
confidence: 53%
“…In our study, PA developed well and PAI was maintained at 485. (10,16,21), PAP, Rp, and SVEDP were similar or lower, whereas PAI was superior in our study. There were no intrapulmonary shunts or atrioventricular valve regurgitations that required intervention by the Fontan procedure.…”
Section: Discussionsupporting
confidence: 48%